Choice Determinants of Donors Giving to Charities - Alexander, Fraser (Auckland University of Technology, 2007)
The research applied multi-criteria decision-making analysis to donor decisions regarding the choice of a particular charity in order to identify which donor attitudes are significant in the giving decision. Factors affecting the appeal of major charities in Health and Disability were compared. The giving decision has not been widely researched overseas and particularly in New Zealand there is a need to do this in order to better manage Not-for-profit marketing resources. 24 factors associated with giving decisions were identified and quantified giving rise to a fully-specified giving model and potentially direct benefits to charitable organizations. The research has made a contribution to our understanding of donor choice determinants and giving models.
Keywords: Charitable donations; Multicriteria decision making; Attitudes; New Zealand charities; Not-for-profit sector marketing